(3efGbH GdNdaGA GdCQHYIs - (3YeQ GdebOSj GdMfajs
(3ChdgG (B:s
(3GdMeO ddg GdPi GNJGQ dQShdg GUMGkHG s
(3cJHJ HQSe GdNRGFf GdTQjaI GdSdWGfjI GdCTQajI GdZhQjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B264 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs